2008
DOI: 10.1111/j.1462-2920.2007.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

The Toll‐like receptors TLR2 and TLR4 do not affect the intestinal microbiota composition in mice

Abstract: The interaction between intestinal epithelial cells and microbes is partly mediated by Toll-like receptors (TLRs). Sensing of Gram-positive and Gram-negative bacteria by TLR2 and TLR4, respectively, can result in immune system activation and in an exclusion of bacteria from the intestine. To test the impact of these TLRs on bacterial composition, germ-free TLR2/TLR4 double-knock out mice and the corresponding C57BL/10ScSn wild-type mice where associated with fecal bacteria from one single donor mouse. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 37 publications
5
29
1
Order By: Relevance
“…A limited number of individuals of the same strain were cocaged to evaluate this effect on cecum bacterial communities. Similar to previous reports (Alexander et al, 2006;Loh et al, 2008;Terán-Ventura et al, 2010), some cagemates were more similar to one another than to isolated mice, but for many no difference was detected. This response varied by mouse and was not strong for most strains.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A limited number of individuals of the same strain were cocaged to evaluate this effect on cecum bacterial communities. Similar to previous reports (Alexander et al, 2006;Loh et al, 2008;Terán-Ventura et al, 2010), some cagemates were more similar to one another than to isolated mice, but for many no difference was detected. This response varied by mouse and was not strong for most strains.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to Friswell et al (2010), we found C3HRI to have low intrastrain variation and BL6J mice to have high intrastrain variation. Gut communities in BL10J mice (Loh et al, 2008) have also been shown to vary among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it will be important in future studies to take into account the physiological amounts of bacterial components and the particular species of commensal bacteria when interpreting data involving exogenous administration of bacteria and/or bacterium-derived components. The role of host immune system such as IgA in the development of the microflora remains controversial (25,42,44). The microflora of NOD1-deficient mice was reported to contain higher numbers of Clostridiales in the ileal biofilm (5), and MyD88-deficient mice contained increased percentages of particular bacteria including Lactobacillaceae and Porphyromonadaceae species (51).…”
Section: Vol 78 2010mentioning
confidence: 99%
“…A denaturing gradient gel electrophoresis and fluorescence in situ hybridization (FISH)-based investigation (Loh et al 2008) and a more recent study using deep 16S rRNA gene surveys both call into question whether TLRs or MyD88 alter the gut microbiota in a genotypedependent fashion (Ubeda et al 2012). Ubeda et al (2012) generated MyD88-, TLR-2-, TLR-4-, TLR-6-, and TLR-9-deficient mouse lines from heterozygote 3 heterozygote breeding strategies.…”
Section: Micementioning
confidence: 99%